High‐dose linaclotide is effective and safe in patients with chronic constipation: A phase III randomized, double‐blind, placebo‐controlled study with a long‐term open‐label extension study in Japan. Issue 1 (23rd October 2018) - Fukudo, Shin; Miwa, Hiroto; Nakajima, Atsushi; Kinoshita, Yoshikazu; Kosako, Masanori; Hayashi, Kenta; Akiho, Hiraku; Kuroishi, Kentaro; Johnston, Jeffrey M; Currie, Mark; Ohkusa, Toshifumi
Abstract: Background: A previous phase II dose‐ranging study of linaclotide in a Japanese chronic constipation (CC) population showed that 0.5 mg was the most effective dose. This study aimed to verify the hypothesis that 0.5 mg of linaclotide is effective and safe in Japanese CC patients. Methods: This was a Japanese phase III randomized, double‐blind, placebo‐controlled (part 1), and long‐term, open‐label extension (part 2) study of linaclotide. CC patients (n = 186) diagnosed using the Rome III criteria were randomly assigned to linaclotide 0.5 mg (n = 95) or placebo (n = 91) for a 4‐week double‐blind treatment period in part 1, followed by an additional 52 weeks of open‐label treatment with linaclotide in part 2. The primary efficacy endpoint was the change from baseline in weekly spontaneous bowel movement (SBM) frequency at the first week. Secondary endpoints included responder rate for complete SBM (CSBM), changes in stool consistency, and severity of straining. Key Results: Part 1: Change in weekly mean SBM frequency in the first week of treatment with linaclotide (4.02) was significantly greater than that with placebo (1.48, P  < 0.001). Linaclotide produced a higher CSBM responder rate (52.7%) compared to placebo (26.1%, P  < 0.001). Part 2: Patients continued to show improved SBM frequency with linaclotide. Through parts 1 and 2, the most common drug‐related adverse event was mild and occasionally moderate diarrhea. Conclusions and Inferences: The results of this study indicate that a linaclotide dose of 0.5 mg/day is effective and safe in Japanese CC patients. Abstract : A previous phase II trial demonstrated that 0.5 mg of linaclotide per day was the most effective dose in Japanese CC patients. This phase III randomized, double‐blind, placebo‐controlled, and long‐term, open‐label extension study of linaclotide in Japanese CC patients clearly indicated that 0.5 mg of linaclotide is effective and safe. This is the fourth replicate study showing that 0.5 mg of linaclotide per day is suitable for constipated Japanese patients.